Marine pollution sources, fate and effects of pollutants in coastal ecosystems - Beiras, Ricardo 1965- (Elsevier, 2018)
"Marine Pollution: Sources, Fate and Effects of Pollutants in Coastal Ecosystems bring together the theoretical background on common and emerging marine pollutants and their effects on organisms (ecotoxicology). Written by a renowned expert in the field who is a researcher, teacher and advisor of national and international institutions on issues such as oil spills, water quality assessment and plastic pollution, this book offers a thorough account of the effects of pollutants on marine organisms, the relevant environmental regulations, and the public health implications, along with the biological tools advocated by the international institutions for marine pollution monitoring. Marine Pollution: Sources, Fate and Effects of Pollutants in Coastal Ecosystems presents information in a detailed and didactic manner, reviewing the latest scientific knowledge alongside examples of practical applications."